(untitled) (Revista Brasileira Multidisciplinar, 2024)
Leishmaniasis is a neglected tropical disease (NTD). In Brazil, the first-choice treatment is meglumine antimoniate (MA), a drug with many adverse effects. The aim of this study was to develop nanostructured lipid carriers (NLC) containing MA for the treatment of leishmaniasis. A pre-formulation study was carried out, including evaluation of the hydrophilic-lipophilic balance (HLB), lipid screening, compatibility studies and qualitative-quantitative planning. The NLC were prepared using the double emulsification method and evaluated for particle diameter, polydispersity index (PdI), zeta potential (ZP) and encapsulation efficiency (EE). The chosen NLC was characterized by transmission electron microscopy (TEM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). It was also tested in vitro to assess cytotoxicity in Raw 264.7 macrophages. The results of the pre-formulation study indicated the choice of Miglyol®812 as the liquid lipid and Alkest® CSO 300 as the best hydrophilic surfactant (HLB= 8.74). The most promising NLC from the planning showed an average diameter of 29 nm, PdI 0.251, PZ -6.76 and EE > 90%. Nanoparticle characterization techniques confirmed the incorporation of MA into the NLC and obtained a less crystalline matrix. MA showed no cytotoxicity in macrophages, while NLC containing the drug was cytotoxic above 19 µg/mL. Therefore, it was possible to obtain NLC with suitable physicochemical properties, high encapsulation efficiency and potential for prolonged release of MA. Studies to evaluate cytotoxicity in leishmania will be carried out.